1984
DOI: 10.1144/gsl.sp.1984.013.01.23
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement of ophiolitic rocks in forearc areas: Examples from central Japan and Izu-Mariana-Yap island arc system

Abstract: Recent results of ocean dredging of ophiolitic rocks in forearc areas in the west Pacific region are summarized and discussed together with the field data in the ophiolitic belts in the Setogawa and Mineoka forearc belts in central Japan. Metamorphism, deformation and sedimentation of the dismembered ophiolites in these regions indicate that they were emplaced at first in transform-fault areas or oceanic fracture zones, and they became the subsequent zones of initiation of subduction. Sometimes the mass of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…They suggest that the outer Mariana forearc contains accreted fragments of Cretaceous oceanic lithosphere, probably extensively faulted and intruded by the products of arc volcanism. Following Ogawa and Naka (1984), we treat the outer forearc as a transform fault terrane intruded by the early products of supra-subduction zone volcanism, similar to that seen on land in the Setogawa and Mineoka forearc belts in Japan and on the island of Yap (see Fig. 1).…”
Section: Oaoga Shima^792mentioning
confidence: 99%
See 2 more Smart Citations
“…They suggest that the outer Mariana forearc contains accreted fragments of Cretaceous oceanic lithosphere, probably extensively faulted and intruded by the products of arc volcanism. Following Ogawa and Naka (1984), we treat the outer forearc as a transform fault terrane intruded by the early products of supra-subduction zone volcanism, similar to that seen on land in the Setogawa and Mineoka forearc belts in Japan and on the island of Yap (see Fig. 1).…”
Section: Oaoga Shima^792mentioning
confidence: 99%
“…In this model, the change from transform motion to subduction coincides with the change in absolute motion of the Pacific plate at about 43 Ma (Clague and Dalrymple, 1987). The second type of map requires that subduction beneath the West Philippine Basin started prior to this change in plate motion (Lewis et al, 1982;Ogawa and Naka, 1984;Seno and Maruyama, 1984;Honza, 1991). To achieve a consistent geometry, Seno and Maruyama (1984) invoke the subduction of an additional plate, the New Guinea plate, beneath the West Philippine Basin.…”
Section: Models For the Initiation Of Subductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karig and Moore (1975) and Ogawa and Naka (1984) hypothesized that the Bonin Islands might be an exotic terrane introduced from the south by oblique motion; however, marine geophysical data indicate their structural continuity with the outer-arc high (Honza and Tamaki, 1985). However interpreted, the magnetic inclination and declination data are essential parameters for reconstructing the initial geometry of the Philippine Sea Plate and its relationship to surrounding plates, and for understanding the conditions that lead to initial subduction along the Izu-Bonin-Mariana Margin and Philippine Sea Plate evolution.…”
Section: Arc/forearc Developments Background To Sites 787 792 and 793mentioning
confidence: 99%
“…One model suggests that the islands acted as "ball-bearings" between the Pacific and Philippine Sea plates. Kang and Moore (1975), and later Ogawa and Naka (1984), suggested that the islands might be an exotic terrain introduced from the south by oblique motion. However, marine geophysical data indicate a structural continuity of the IzuBonin Islands with the outer-arc high (Honza and Tamaki, 1985) and support Keating et al's model (1983) that the Izu-Bonin Islands (and therefore the Philippine Sea Plate) were situated near the Equator during the Eocene, roughly perpendicular to their present trend.…”
mentioning
confidence: 99%